1996
DOI: 10.1001/archinte.1996.00440180095012
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Affect and Survival Among Gay and Bisexual Men Infected With HIV

Abstract: Depressive affect was associated with mortality risk, highlighting the importance of diagnosis and treatment of depression among HIV-infected gay and bisexual men. Replication of this effect in incident cohorts with well-characterized dates of HIV infection is needed and, if replicated, an exploration of mediating pathways suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(40 citation statements)
references
References 34 publications
2
37
0
1
Order By: Relevance
“…Thus, specific impairments in NK cell function may compromise the host's natural resistance against HIV. These HIV effects on NK cell function, coupled with the reports of reduced NK cell activity in depression, including depressed HIV-infected individuals, could underlie the findings from studies suggesting that depression adversely affects HIV disease progression in prospective clinical investigations of HIV-seropositive individuals (11,13,14,17,18,(86)(87)(88).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, specific impairments in NK cell function may compromise the host's natural resistance against HIV. These HIV effects on NK cell function, coupled with the reports of reduced NK cell activity in depression, including depressed HIV-infected individuals, could underlie the findings from studies suggesting that depression adversely affects HIV disease progression in prospective clinical investigations of HIV-seropositive individuals (11,13,14,17,18,(86)(87)(88).…”
Section: Discussionmentioning
confidence: 97%
“…Increasing evidence suggests that depression is a potential risk factor for the morbidity and mortality in other medical diseases, including HIV/AIDS (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Depression has been associated with alterations in cellular immunity, including NK cell numbers and NK cell cytotoxicity (20)(21)(22)(23)(24) in individuals who are depressed but without other medical illnesses.…”
mentioning
confidence: 99%
“…To our knowledge, this is the first time that changes in dietary intake have been associated with depression in persons with HIV. Depression has been associated with increased mortality in a number of studies [39][40][41][42] , but the mechanisms that might explain the association are not known. Our findings suggest that poor nutrition should be explored as a potential contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…In several PNI-related studies with the HIV-infected population, clear associations have been demonstrated between psychological distress and immunosuppression or disease progression (e.g., Antoni, 2003;Herbert & Cohen, 1993;Leserman et al, 2002;Mayne, Vittinghoff, Chesney, Barrett, & Coates, 1996;Patterson et al, 1996). Such relationships could be due to a number of causal factors, including declines in lymphocyte function and numbers, altered expression of immunoregulatory cytokines, changes in neuropeptide or hormone levels (particularly cortisol), and reduced NKC or T-lymphocyte cytotoxicity (Bollinger & Siliciano, 1992;Pitzalis et al, 1997;Rosenberg, Anderson, & Pabst, 1998).…”
Section: Introductionmentioning
confidence: 99%